2017
DOI: 10.1155/2017/9314026
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Physical Activity and Physical Fitness in Preschool Children: A Cross-Sectional Study

Abstract: Purpose To evaluate the relationships between objectively measured physical activity and physical fitness among preschool children. Methods A total of 346 participants (201 boys and 145 girls) aged 3.5–5.5 years (M = 4.5 yr, SD = 0.47) from Shanghai, China, completed physical fitness assessments, including triceps skinfold thickness (TSFT), grip strength, tennis throwing, sit and reach test, standing long jump, balance beam, 10mSRT, and 20mSRT. Physical activity was objectively measured by ActiGraphGT3X+ accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 35 publications
8
59
3
6
Order By: Relevance
“…The aspect of physical fitness is an important part of supporting physical activity and as a measure of one's health. Fang et al [8] revealed the importance of physical fitness as an effort to prevent obesity in children. Furthermore, Ortega et al [10] added that the level of physical fitness had a positive effect on reducing depression, anxiety, and supporting higher academic performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aspect of physical fitness is an important part of supporting physical activity and as a measure of one's health. Fang et al [8] revealed the importance of physical fitness as an effort to prevent obesity in children. Furthermore, Ortega et al [10] added that the level of physical fitness had a positive effect on reducing depression, anxiety, and supporting higher academic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Research on physical fitness has been carried out and shows the relationship between physical fitness and physical activity undertaken [7][8][9]. However, there is still few researches that concerns on physical fitness in Physical Education.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings support the research hypothesis, a n d are with previous studies indicating that PA was significantly associated with physical fitness in preschool children. Data from cross-sectional studies suggested active children were more likely to have better physical fitness than less active [11] and sedentary behavior children [43]. Vigorous PA was also found beneficial to CRF, a s children who accumulated 40 min vigorous PA was greater than those only had 18 min [44].…”
Section: Comparison With the Findings From The Previous Publicationsmentioning
confidence: 99%
“…PA is regarded as a basic component of healthy lifestyles [10], which facilitates the preschooler's CRF, musculoskeletal fitness, a n d motor fitness [11][12][13]. To achieve health benefits from regular PA participation, the U.S. [14], Canada [15], Australia [16], a n d the World Health Organization (WHO) [17] have issued specific PA guidelines for preschool children, which have stated that preschoolers should engage in ≥ 180 min per day in PA of all intensity levels, including ≥60 min of moderate-to-vigorous physical activity (MVPA).…”
Section: Introductionmentioning
confidence: 99%
“…Vztah pohybové aktivity a tělesné zdatnosti je u dětské populace mnohem problematičtější než se obecně předpokládá [6]. Pohybová aktivita přispívá k úrovni tělesné zdatnosti u dospělých jedinců, ale u dětské populace není tento vztah tak silný.…”
unclassified